The potential of toe flexor muscles to enhance performance - Goldmann, J.-P.; Sanno, M.; Willwacher, S.; Heinrich, K.; Brüggemann, G. P. (Journal of Sports Sciences, 2013)
The metatarsal phalangeal joint (MPJ) and its crossing toe flexor muscles (TFM) represent the link between the large energy generating leg extensor muscles and the ground. The purpose of this study was to examine the functional adaptability of TFM to increased mechanical stimuli and the effects on walking, running and jumping performance.